2019
DOI: 10.1016/j.jmb.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The interdimeric interface controls function and stability of Ureaplasma urealiticum methionine S-adenosyltransferase

Abstract: Methionine S-adenosyltransferases (MATs) are predominantly homotetramers, comprised of dimers of dimers. The highly conserved dimeric interface harbors two active sites, making the dimer the obligatory functional unit. Yet, functionality of the recently evolved inter-dimeric interface remains unknown. Here, we show that the inter-dimeric interface of U. urealiticum MAT has evolved to control the catalytic activity and structural integrity of the homotetramer in response to product accumulation. When all four a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…The unfolding data also show that the dimer of PCP6 is more stable than that of PCP7 or of PCP-CA, where the mid-point of dimer dissociation is approximately 5 M urea for PCP6 versus 2 M urea for PCP7 and PCP-CA, likely due to the higher population of the I2 intermediate in PCP6 compared to PCP7 and PCP-CA. Notably, Matthews and others (42,43) have reported that amino acid substitutions that change in the number of salt bridges in the native structure of a protein are a key parameter in modulating the free energy landscape of a protein fold. We compared the number of salt bridges among extant caspases using a protein tool developed by Ferruz et al (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfolding data also show that the dimer of PCP6 is more stable than that of PCP7 or of PCP-CA, where the mid-point of dimer dissociation is approximately 5 M urea for PCP6 versus 2 M urea for PCP7 and PCP-CA, likely due to the higher population of the I2 intermediate in PCP6 compared to PCP7 and PCP-CA. Notably, Matthews and others (42,43) have reported that amino acid substitutions that change in the number of salt bridges in the native structure of a protein are a key parameter in modulating the free energy landscape of a protein fold. We compared the number of salt bridges among extant caspases using a protein tool developed by Ferruz et al (44).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Matthews et al. ( 42 , 43 ) have reported that amino acid substitutions that change in the number of salt bridges in the native structure of a protein are a key parameter in modulating the free energy landscape of a protein fold. We compared the number of salt bridges among extant caspases using a protein tool developed by Ferruz et al.…”
Section: Discussionmentioning
confidence: 99%
“…In case of MAT enzymes, the constituent monomers pair up in an inverted configuration by exposing the α-helices towards the surface and the β-strands interact to form a hydrophobic isologous large interface that harbor the catalytic residues – thereby making this homo-dimer the obligate functional unit 27 . Herein, we notice that divergence is not just limited to catalytic residues, or the residues located close to the substrate, but most of the inter-dimer interface (large-interface) residues are also quite diverged across the three domains of life, for instance - in case of bacteria (eMAT, PDB: 1RG9, 28 ) and eukarya (hMAT1A, PDB:6SW5, 29 ) - 38 out of 51 aligned residues are identical.…”
Section: Resultsmentioning
confidence: 99%
“…The unfolding data also show that the dimer of PCP6 is more stable than that of PCP7 or of PCP-CA, where the mid-point of dimer dissociation is approximately 5 M urea for PCP6 versus 2 M urea for PCP7 and PCP-CA, likely due to the higher population of the I2 intermediate in PCP6 compared to PCP7 and PCP-CA. Notably, Matthews and others (40,41) have reported that amino acid substitutions that change in the number of salt bridges in the native structure of a protein are a key parameter in modulating the free energy landscape of a protein fold. We compared the number of salt bridges among extant caspases using a protein tool developed by Ferruz et al (42).…”
Section: Discussionmentioning
confidence: 99%